La pose de l’épicier. Reportage ethnographique dans les épiceries grecques et turques de Bruxelles - Katerina Seraïdari (Images du Travail, Travail des Images)
This article examines how a photographic corpus allows to better understand the multifaceted nature of grocer’s work. In this framework, photography, that functions as “a mechanism of apparition”, brings to light behind every move, a profession and its complexity. The iconographic analysis reveals thus the place that these economic actors occupy in the neighbourhood, but also in the urban space: their role, which often goes beyond the economic sphere, interrogates the notion of “relational work”, but also the distinction between boutiques and services.